A Novel Approach for Repetitive Dislocation of Transvenous Left Ventricular Leads During Cardiac Resynchronization Therapy Implantation by the Loop Technique - Wu, Hao-Yu; Li, Shang-Jian; Yang, Zheng; Chen, Hai-Chao; You, Peng-Hua; Cheng, Gong (Frontiers in Cardiovascular Medicine, 2022)
Cardiac resynchronization therapy (CRT) for heart failure requires transvenous insertion of a left ventricular pacing lead through the coronary sinus. However, repeated intraoperative dislocations often occur. Therefore, we describe a novel technique that uses the loop technique to treat patients with repeated intraoperative dislocations during transvenous left ventricular lead implantation to stabilize the lead in its final position. In five patients with repeated intraoperative dislocation during transvenous left ventricular lead implantation, the loop technique was successfully used to stabilize the lead in its final position. The pacing and sensing parameters were satisfactory in all patients at implantation and 12 months post-operatively. Compared with the pre-operative values, the 12-month post-operative values for the left ventricular ejection fraction were significantly increased and the left ventricular end systolic dimension and left ventricular end diastolic dimension were significantly decreased (P < 0.05). The left ventricular ejection fraction of these 5 patients increased by more than 15%. CRT significantly improved the left ventricular structure and function of these 5 patients. During the 1-, 3-, 6-, and 12-month follow-ups, no left ventricular lead dislocations were observed. This loop technique is safe and effective and can be considered for repeated intraoperative dislocation during transvenous left ventricular lead implantation through the coronary sinus of a CRT device.